MANAGING THE DILEMMA OF FAITH AND EXTRACTIVISM: MODELLING GOOD MINING GOVERNANCE FOR RELIGIOUS CIVIL SOCIETY ORGANISATIONS IN INDONESIA - Mustofa, Mustabsyirotul Ummah (Universitas Padjadjaran, 2025)
Mining or extractive industries not only provide opportunities for countries that have natural resources, but also provide challenges related to their management. This research departs from the granting of mining concessions for religious CSOs in Indonesia in 2024, which were received by Nahdlatul Ulama and Muhammadiyah. The granting of this mining concession raises controversy where religious CSOs are globally involved in the discourse of promoting environmental justice, on the contrary, NU and Muhammadiyah are part of the source of environmental justice problems, namely mining. This research seeks to find a mining governance model for these religious CSOs when policy is not possible to change. By conducting a theoretical literature review of concepts with the keywords mining governance, extractive governance, natural resource governance, the researcher synthesises the key elements that need to be present in the mining governance model for religious CSOs for the Indonesian context.The results of the research indicate that the following elements are required for the governance of religious CSOs in the context of mining: governance legitimacy, distributive justice, socio-environmental responsibility, transparency and accountability, and multi-stakeholder engagement. It is imperative that each core element is implemented by religious CSOs, given their role in civil society, which is distinct from their function as mining companies. It is imperative that this is carried out so that religious CSOs do not lose public trust and can serve as a model for sustainable mining governance for countries that possess abundant natural resources but have failed to achieve sustainable development (resource curse). Industri pertambangan atau ekstraktif tidak hanya memberi peluang bagi negara yang memiliki sumber daya alam, tetapi juga menghadirkan tantangan besar dalam pengelolaannya. Penelitian ini berangkat dari kebijakan pemerintah Indonesia yang memberikan konsesi tambang kepada Organisasi Kemasyarakatan (Ormas) Keagamaan pada tahun 2024, khususnya Nahdlatul Ulama dan Muhammadiyah. Kebijakan ini menuai kontroversi karena secara global ormas keagamaan dikenal aktif mendorong keadilan lingkungan, namun kini justru berpotensi menjadi bagian dari sumber masalah melalui keterlibatan langsung dalam kegiatan pertambangan. Penelitian ini bertujuan merumuskan model tata kelola pertambangan yang relevan bagi ormas keagamaan ketika perubahan kebijakan tidak dapat dilakukan dalam waktu dekat. Dengan menggunakan tinjauan literatur sistematis terhadap konsep mining governance, extractive governance, dan natural resource governance, penelitian ini menyintesis elemen-elemen penting yang perlu diadopsi agar tata kelola pertambangan oleh ormas dapat berkelanjutan dan selaras dengan nilai-nilai keagamaan. Hasil penelitian menunjukkan lima elemen utama yang harus diterapkan: legitimasi tata kelola, keadilan distributif dalam pemanfaatan manfaat ekonomi, tanggung jawab sosial dan lingkungan untuk meminimalkan dampak negatif, transparansi dan akuntabilitas dalam setiap proses pengelolaan, serta keterlibatan multi-pemangku kepentingan, termasuk masyarakat terdampak. Penerapan kelima elemen ini menjadi keharusan, mengingat posisi ormas keagamaan sebagai bagian dari masyarakat sipil yang memiliki fungsi moral dan sosial, bukan sekadar aktor ekonomi. Dengan tata kelola yang tepat, ormas keagamaan diharapkan tidak kehilangan kepercayaan publik serta mampu menjadi model praktik pertambangan berkelanjutan bagi negara-negara dengan sumber daya alam melimpah namun masih menghadapi tantangan kutukan sumber daya (resource curse).